Implementation of Moderate Religious Values Through the Application of the Scout Movement Code of Honour Among Students at UKMK Pramuka - Herlica Agustina; Abdurrahmansyah, Abdurrahmansyah; Firmansyah, Firmansyah; Syarif Zain, Zaki Faddad; Alimron, Alimron (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
The discussion of religious moderation is becoming increasingly important amid various deviations that distort its essence. In today’s context, challenges such as radicalism and extremism threaten the balance of religious life. Therefore, strengthening religious moderation through education is essential to nurture a generation that upholds tolerance and harmony in Indonesia. Instilling moderation values can be achieved through both formal and non-formal education, one of which is the Scout Movement. Scouting activities aim to foster brotherhood, friendship, and unity, making them an effective medium for applying moderation values. In universities, scouts play a vital role in uniting students as future leaders who embody and spread the spirit of moderation. This research employs a qualitative descriptive approach using interviews with seven informants to explore how the Scout Movement’s code of honor reflects the practice of religious moderation among students. The results indicate that moderation values have been well implemented by scout members at UIN Raden Fatah Palembang through regular programs, social service, outdoor activities, and leadership training. Adherence to the scout code of honor serves as an ethical guideline that shapes members’ behavior, encouraging them to act responsibly and uphold the principles of religious moderation.